Spatial navigation under threat: aversive apprehensions improve route retracing in higher versus lower trait anxious individuals - Bublatzky, Florian; Allen, Peter; Riemer, Martin (Frontiers in Psychology, 2023)
Spatial navigation is a basic function for survival, and the ability to retrace a route has direct relevance for avoiding dangerous places. This study investigates the effects of aversive apprehensions on spatial navigation in a virtual urban environment. Healthy participants with varying degrees of trait anxiety performed a route-repetition and a route-retracing task under threatening and safe context conditions. Results reveal an interaction between the effect of threatening/safe environments and trait anxiety: while threat impairs route-retracing in lower-anxious individuals, this navigational skill is boosted in higher-anxious individuals. According to attentional control theory, this finding can be explained by an attentional shift toward information relevant for intuitive coping strategies (i.e., running away), which should be more pronounced in higher-anxious individuals. On a broader scale, our results demonstrate an often-neglected advantage of trait anxiety, namely that it promotes the processing of environmental information relevant for coping strategies and thus prepares the organism for adequate flight responses.